Mechanical properties (compression) of sawdust concrete in different additives - Mohd Zaharin, Tarudin (2014)
Increase in prices of raw materials for the construction industry resulted in the use of recycled materials as an alternative for replacing the conventional materials. One of that is sawdust that has a potential in application of lightweight concrete. However the problem that identified in sawdust cement concrete is an incompatibility between cement and wood in other to form a concrete. The presence of substance was found as inhibitor which retards the hydration and the hardening of cement process. In order to form the sawdust concrete, additives and mixing ratio is very important so that the concrete created will meet the desired quality. Hence, the main objective for this research is to determine the compressive strength of sawdust concrete as a full replacement coarse aggregate with different additives and different mix ratio of additives. The other objective is to study the effect of additives when mixed in the sawdust concrete. The methodology of this research consist three stages; collect data, samples preparation and testing. Four type of mixture were tested for compression test. Those are control sample, sawdust with lime, sawdust with cockle shell and sawdust with spent bleaching earth (SBE). The total samples are 90 samples for 7,14 and 28 days of strength. The highest 28 day compressive strength was achieved by 1:1:3:1 (lime) mix proportion which is 5.27 Mpa. Meanwhile the lowest 28 days compressive strength was achieved by 1:1:3:0.33 (SBE) which is 1.84 Mpa. According from that, it shows that sawdust concrete with different additives in having different mix ratio has a potential in the lightweight concrete industry.